Solubility of carbon dioxide in aqueous solution of 1, 5-diamino-2-methylpentane: Absorption and desorption property. (August 2016) - Azhgan, M.; Farsi, M.; Eslamloueyan, R.
Highlights: The 1, 5-diamino-2-methylpentane (DAMP) is introduced as novel CO2 absorbent. CO2 loading is measured at the temperature range 30–50 °C and different solvent concentrations. The absorption rate, desorption and cyclic capacity of DAMP is measured. Abstract: This research focuses on carbon dioxide absorption using aqueous solution of 1, 5-diamino-2-methylpentane (DAMP) in an isothermal batch reactor. Equilibrium CO2 loading by the proposed aqueous solution is measured at the temperature range 30–50 °C, CO2 partial pressure range 5–150 kPa, and different solvent concentrations. To prove the performance of the proposed diamine to capture CO2, absorption and desorption capacity, absorption rate and cyclic capacity of 1, 5-diamino-2-methylpentan is measured and compared with MEA and MDEA. The experimental results show that the equilibrium CO2 loading of 1, 5-diamino-2-methylpentane, MDEA and MEA are 0.86, 0.43 and 0.54 at 30 °C, respectively. Lower volatility of 1, 5-diamino-2-methylpentane compared to MEA results in a lower solvent loss through CO2 removal process. Applying the proposed amine in the absorption towers can decrease solvent circulating rate and required equilibrium stages.